1963
DOI: 10.1039/df9633600169
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectra and related ionic effects in gamma-irradiated organic glassy solids

Abstract: Garmna irradiation at 77°K of organic glassy solids which contain solutes RX or M provide evidence for the formation of R and X-by dissociative electron attachment, M-by simple electron attachment and M+ by charge exchange with appropriate components of the matrix. Benzyl chloride and naphthalene illustrate the two types of solute. Detection in all cases was based upon electronic absorption spectra. Failure to observe M+ in ethanol and other polar media indicates efficient formation of such protonated species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1965
1965
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The benzyl radicals were generated by the direct photolysis of diphenylacetone (1) in MeCN, PC, DMF and DMSO. Solutions of 3 × 10 −3 , 6 × 10 −3 or 9 × 10 −3 M were slowly flowed (1-2 ml/min) through the cell, after carefully degassing the solution with argon.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benzyl radicals were generated by the direct photolysis of diphenylacetone (1) in MeCN, PC, DMF and DMSO. Solutions of 3 × 10 −3 , 6 × 10 −3 or 9 × 10 −3 M were slowly flowed (1-2 ml/min) through the cell, after carefully degassing the solution with argon.…”
Section: Methodsmentioning
confidence: 99%
“…The generation of benzyl radical and substituted benzyl radicals can be performed by a large variety of methods like γ-radiolysis [1], pulse radiolysis [2], electrolysis [3], hydrogen abstraction [4][5][6] but the most popular method remains photolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Hamill et al (97), continuing earlier post-irradiation spectroscopic studies of ions in glasses, have observed both dissociative electron attach ment and electron capture by solutes. Triphenylmethyl chloride and benzyl chloride in tetrahydrofuran glasses exhibit the former, while napthalene and biphenyl in 3 methyl pentane, 2 methylpentene-1 glasses exhibit the latter.…”
Section: Ions and Ionic Reactionsmentioning
confidence: 95%
“…Hamill et a1. (97) have observed several absorption spectra in hydrocarbon glasses containing aromatic hydro carbon solutes. The difference in absorption spectra between 3-methylpentane glasses with and without 25 per cent 2-methylpentene-l added are attributed to hydrogen atom adducts with the aromatic hydrocarbons.…”
Section: Free Radical Processesmentioning
confidence: 97%
“…absorption of trapped electrons in polar glasses, such as alkaline ice (1 -3), alcohols (4)(5)(6)(7)(8)(9)(10)(11)(12), water-alcohol mixtures (13)(14)(15), and methyltetrahydrofuran (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). One objective of scavenger studies has been to produce new anions from the reaction of the mobile electron with the scavenger molecule.…”
mentioning
confidence: 99%